The Role of Biomarker Genes in the Diagnosis and Treatment of Non-small Cell Lung Cancer - Sokouti, Massoud; Sokouti, Mohsen; Sokouti, Babak (Current Respiratory Medicine Reviews, 2018)
Lung cancer has been recognized as the most important reason for death and a lifethreatening disease. The late diagnosis of this disease usually limits treatment interventions. The lack of reliable noninvasive biomarkers and therapies results in low survival rates. The current review is designed to uncover the specific role of biomarker genes involved in the non-small cell lung cancer (NSCLC) and demonstrate their high discrimination power between NSCLC from the normal tissues. So, studying the gene expression differences associated with their network functionality extracted from the serum biomarkers will be a helpful approach in predicting them on small cell lung cancer. Nowadays, several analyses based on bioinformatics and computational methodologies have determined various genes influencing the healthy and diseased cells for achieving a better performance on treatment and prognosis of NSCLC. Although the existing treatments for all stages of lung cancer including surgery, chemotherapy, or radiation did not show reasonable results, achieving better outcomes in the future may be possible through genetic diagnosis as well as gene therapy techniques.
Keywords: treatment